Reshaping Maine Woods Destinations for Twenty-First-Century Tourists - Vail, David; Moreland, Donna; Wilson, Mike (Maine Policy Review, 2019)
Maine’s rim counties—here called the Maine Woods region—suffer from chronic economic and community distress, marked by declines in several resource-based industries, an ongoing youth exodus, and a rapidly aging population. Nonetheless, many encouraging new ventures are helping to revitalize the Maine Woods economy and communities, and tourism and recreation should play a central role in these efforts. This article focuses on initiatives launched through a partnership between the 16-member Maine Woods Consortium and the Maine Office of Tourism designed to reinvigorate Maine Woods’ recreation and hospitality offerings and to enrich amenities in the region’s gateway communities.
Keywords: Maine; tourism; rural; rim counties